PROGRAM GERAKAN PEMBANGUNAN KAMPUNGKU DI KABUPATEN MERAUKE - Leo Antonio (SOCIETAS, 2014)
In general, a program to stimulate innovation is accelerating development and economic development in the region , especially the empowerment villages and involve the participation and the participation of all elements of society in order to hone the potential of human resources development and progress . This study aims to determine the course my gate in Merauke whether it can be categorized as an innovation , knowing the level of innovation and impact performance . The method used in this research is descriptive quantitative survey research design , techniques of data collection is done through questionnaires / questionnaire .The results showed that the program my gate can not be categorized as an innovative program . Innovation variables , the level of innovation , and the results show the impact of innovation programs is still low . The impact of the program does not provide a positive contribution to the quality of life and the prominent communities in the village .